The potential effect of metformin on cognitive and other symptom dimensions in patients with schizophrenia and antipsychotic-induced weight gain: a systematic review, meta-analysis, and meta-regression - Battini, Vera; Cirnigliaro, Giovanna; Leuzzi, Rodolfo; Rissotto, Eleonora; Mosini, Giulia; Benatti, Beatrice; Pozzi, Marco; Nobile, Maria; Radice, Sonia; Carnovale, Carla; Dell’Osso, Bernardo; Clementi, Emilio (Frontiers in Psychiatry, 2023)
Introduction Metformin has shown good efficacy in the management of antipsychotic-induced metabolic syndrome (MetS) in patients with schizophrenia or schizoaffective disorders. Its ability to induce antidepressant behavioural effects and improve cognitive functions has also been investigated: yet information has not been systematized. The aim of this study was therefore to investigate the effects of metformin on cognitive and other symptom dimension in schizophrenic patients treated with antipsychotics through a systematic review and meta-analysis. Methods We searched PubMed, ClinicalTrials.Gov, Embase, PsycINFO, and WHO ICTRP database up to February 2022, Randomised Controlled Trials (RCT) evaluating patients diagnosed with schizophrenia and related disorders, who were treated with metformin as add-on therapy to antipsychotics for the treatment of weight gain and in which changes in psychiatric symptoms and cognitive functions were evaluated. Results A total of 19 RCTs met the inclusion criteria. Meta-analysis was performed on 12 eligible studies. We found a positive trend after 24 weeks of treatment in schizophrenic patients with stable conditions [SMD (95%CI) = -0.40 (−0.82;0.01), OR (95%CI) = 0.5 (−2.4;3.4)]. Better performance was detected in the Brief Assessment of Cognition in Schizophrenia and Positive and Negative Syndrome Scale (PANSS) with low heterogeneity among studies. One study reported changes in BACS-verbal memory subdomain in favour of placebo [MD (95%CI) = -16.03 (-23.65;8.42)]. Gastrointestinal disorders, xerostomia, and extrapyramidal syndrome were the most reported adverse effects. Psychiatric adverse events were also described: in particular, symptoms attributable to a relapse of schizophrenia. Conclusion Some degree of efficacy was found for Metformin in improving cognitive and other symptom dimensions in patients with Schizophrenia. Given the clinical relevance of this potential pharmacological effect, longer specific studies using adequate psychometric scales are strongly recommended. Likewise, how metformin acts in this context needs to be evaluated in order to enhance its efficacy or find more efficacious drugs.